2007
DOI: 10.1002/ajh.21020
|View full text |Cite
|
Sign up to set email alerts
|

Oral decitabine reactivates expression of the methylated γ‐globin gene in Papio anubis

Abstract: The silencing of tumor suppressor genes associated with increased DNA methylation of the promoter regions is a frequent observation in many forms of cancer. Reactivation of these genes using pharmacological inhibitors of DNA methyltransferase such as 5-aza-29-deoxycytidine (decitabine) is a worthwhile therapeutic goal. The effectiveness and tolerability of low-dose intravenous and subcutaneous decitabine regimens to demethylate and reactivate expression of the methylated c-globin gene in baboons and in patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 33 publications
(32 reference statements)
1
19
0
Order By: Relevance
“…Comparison of the level of γ-globin synthesis in RN-1-treated baboons with previous results from our laboratory of baboons treated with DNMT inhibitors [3][4][5]12,38,[40][41][42] A. Rivers et al 694 haematologica | 2016; 101(6) …”
Section: Discussionmentioning
confidence: 74%
“…Comparison of the level of γ-globin synthesis in RN-1-treated baboons with previous results from our laboratory of baboons treated with DNMT inhibitors [3][4][5]12,38,[40][41][42] A. Rivers et al 694 haematologica | 2016; 101(6) …”
Section: Discussionmentioning
confidence: 74%
“…(19). By contrast, studies in baboons using oral decitabine and decitabine mesylate achieved similar re-expression of fetal hemoglobin to that observed with subcutaneously administered DAC, suggesting that these agents may be more effectively absorbed (20). As yet there are no published reports for these orally administered drugs in humans.…”
Section: Dna Methyltransferase Inhibitorsmentioning
confidence: 94%
“…However, Eli Lilly has developed a gemcitabine prodrug that is currently in clinical trials. Although no decitabine prodrugs are currently in clinical trials, it has been demonstrated that with appropriate oral dosing, it is possible to achieve pharmacologically relevant plasma concentrations for cancer treatment (17). Since the dose of decitabine needed to inhibit HIV replication is expected to be lower, it is possible that a prodrug would not be needed, although without a prodrug, it is likely that decitabine would have to be taken multiple times per day, which is not reasonable for anti-HIV drugs.…”
Section: Figmentioning
confidence: 99%